Assessment of breastfeeding position and attachment (ABPA) in a tertiary care centre in Chennai, India: an observational descriptive cross-sectional study - Aswathaman, Nalini; Sajjid, Mohamed; Kamalarathnam, C. N.; Arasar Seeralar, A. T. (International Journal of Contemporary Pediatrics, 2018)
Background: Effective breastfeeding becomes an art with experience. Correct position and attachment is the first step necessary for exclusive breast feeding. However, studies assessing correct position and attachment for breastfeeding in South India are sparse. Hence our study aimed to assess the percentage of mother infant dyads with correct breastfeeding position and attachment along with factors influencing them in a Tertiary care Hospital. Methods: A descriptive cross-sectional study was conducted among the stable dyads in Institute of Obstetrics and Gynaecology using quasi random sampling. 101 dyads were observed for correct position, attachment and effective suckling using WHO B-R-E-A-S-T feed observation form and were scored. Data was analyzed using SPSS software with chi square test, univariate logistic regression and spearman correlation test. Results: Among the 101 dyads, only 30.7% of them had good or average position, 52.47% had good or average attachment and 62.3% had effective suckling at breast. There was significant correlation between breast problem in mother with incorrect position and poor attachment. NICU stay and breast problems were significantly associated with poor attachment. Effective suckling improved significantly as gestational age matured and in infants who had no NICU stay. Conclusions: Practical demonstration on how to hold infants in correct breastfeeding position and drilling with key points for correct position and attachment as soon as possible after delivery will go a long way for promoting exclusive and effective breastfeeding by learning correct technique. Rechecking after counselling will reinforce this learned art.